Peran Universitas dalam Mendukung Pencapaian SDGs - Cowen Effendi; Mardiana Mardiana (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2024)
Sustainablity is defined as the process of organizations striving to improve the quality of life in their community by balancing economic, social, and environmental factors. A university that excels in knowledge creation and dissemination, while also mobilizing resources to meet socio-economic and environmental needs in an ethical and effective manner, is considered a Sustainable University. Education for Sustainable Development aims to teach students the necessary competencies to drive social, economic, and political change and promote sustainable development. A sustainable future is crucial for our societies and planet, as it considers economic growth, social inclusion, and environmental protection. The UI GreenMetric World University Ranking evaluates universities' environmental commitments and initiatives through 39 indicators in 6 criteria to determine their green campus and environmental keberlanjutan rankings. The research uses a literature review to provide a general understanding of the topic. This research uses literature review for data collection. This research focuses on the top 10 UI GreenMetric universities for research purposes. The article discusses the role of Indonesia's top 10 universities in supporting the Sustainable Development Goals (SDGs). The study uses the UI GreenMetric World University Ranking system to assess the keberlanjutan performance of these universities. The findings show that all of the universities are making progress towards sustainability, but there is still room for improvement.